Acclimatization of Micro Shoot-tip Cutting Red Palestine Fig on Several Planting Media Compositions - Erfa, Lisa; Hamiranti, Rahmadyah; Maulida, Desi (Politeknik Negeri Bengkalis, 2024)
Acclimatization is a critical stage in plant micropropagation. Many plantlets resulting from tissue culture cannotsurvive when acclimatized. External environmental conditions will affect the ability of acclimatized plants to survive. Apart from climatic conditions (temperature and sun intensity), the type of media and its composition of the planting mediacan also influence the ability of plantlets to survive and grow. This research aims to: 1) see effect of media plantingcomposition on acclimatization of fig micro shoot-tip cutting, and 2) find the best composition of acclimatization mediatreament for the success and growth of acclimatized fig from micro shoot-tip cutting. The research was carried out using aRandomized Block Design with 7 treatments, and each treatment was repeated 4 times. Each experimental unit was plantedwith 6 cuttings of fig plants resulting from in vitro multiplication. The data were subjected to analysis of variance, anddifferences between acts were tested with Tukey Test at the 5% level. The results showed: 1) The media plantingcomposition were success to influence acclimatization of fig micro shoot-tip cutting, 2) The best composition ofacclimatization media treament for the success and growth of fig micro shoot-tip cutting is top soil+cocopeat, and 3) Thehighest percentage of survival rate on fig micro shoot-tip cutting acclimatization (75%) obtained on top soil+cocopeatmedia followed by top soil media (45%).